Penerapan Model Pembelajaran Problem Based Learning Berbantuan Permainan Edukatif untuk Meningkatkan Hasil Belajar Matematika Pada Materi Data Di Kelas V B SDN 105 Pekanbaru - Pratiwi, Wira; Syafitri, Amelia; Misel, Jihan Salsabillah; AlHafizh, Muhammad Ichsan; Khairunnisa, Putri Rima; Sari, Intan Katika; Dewi, Kusmega (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
The purpose of this study was to determine whether the PBL learning model assisted by educational games could improve students' learning outcomes on the subject of flat shapes. This research was conducted in class V B SDN 105 Pekanbaru. The subjects of this study were 33 students which including 19 male students and 14 female students. The research model applied was classroom action research, consisting of two cycles. The teaching and learning process in each cycle is composed of four stages, namely: planning, implementation, observation, and reflection. The data in this study were obtained through tests and observations and then analyzed using descriptive presentation techniques. Based on the results of data analysis obtained in cycle 1, the average learning outcomes obtained by students were 83.0, with a percentage of completeness of 84.6%. The average learning outcomes of students in cycle 2 increased to 85.5, with a percentage of completeness of 91%. The percentage of completeness in cycle 2 is relatively large, which shows that the application of the PBL model assisted by educational games can advance students' mathematics learning outcomes on the subject of data.